2017
DOI: 10.1167/iovs.17-22264
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Progression, and Risk Factors for Cataract in Type 2 Diabetes

Abstract: PURPOSE.We report the 4-year incidence, progression, and risk factors of cataract subtypes in type 2 diabetes. METHODS.A total of 779 subjects completed baseline and 4-year follow-up.RESULTS. The incidences of nuclear opalescence (NO), nuclear color (NC), cortical cataract (CC), and posterior subcapsular cataract (PSC) were 70%, 55.2%, 25.7%, and 7.3%, respectively. One-step progressions of NO, NC, CC, and PSC were 14.3%, 16.1%, 8.8%, and 8.1%, respectively, and two-step or more progressions were 5.0%, 6.0%, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 51 publications
3
48
1
1
Order By: Relevance
“…Three observational studies found diabetes duration was associated with cataract. An increased odds (OR 1.1 [95%CI: 1.0‐1.2] per year, P = 0.01) of PSC cataract was found with increasing diabetes duration in the SN‐DREAMS II study . However, this study did not have a baseline ophthalmic assessment so differentiation between prevalent and incident cataract was not possible, and there were limited variables included in the regression analysis.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Three observational studies found diabetes duration was associated with cataract. An increased odds (OR 1.1 [95%CI: 1.0‐1.2] per year, P = 0.01) of PSC cataract was found with increasing diabetes duration in the SN‐DREAMS II study . However, this study did not have a baseline ophthalmic assessment so differentiation between prevalent and incident cataract was not possible, and there were limited variables included in the regression analysis.…”
Section: Discussionmentioning
confidence: 91%
“…The worst eye was generally used in analyses. One study did not compare those with cataracts to those with no cataracts, instead comparing those with versus without one sub‐type …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations